Cytokine interactions and chemokine dysregulations in mastitis immunopathogenesis: insights from transcriptomic profiling of milk somatic cells in tropical Sahiwal (Bos indicus) cows - Satheesan, Lija; Dang, Ajay Kumar; Alex, Rani (Frontiers in Immunology, 2025)
IntroductionBovine mastitis causes a significant loss to the dairy industry by affecting the quantity and quality of milk. Addressing this challenge, the present study will leverage advanced omics techniques for early mastitis detection in early lactating Sahiwal cows (Bos indicus). This was the first differential transcriptomic study investigating the alterations in gene expression in milk somatic cells during the progression of naturally occurring mastitis in indigenous Sahiwal cows.MethodsCows were grouped into healthy (H), subclinical mastitis (SCM) and clinical mastitis (CM) groups by thoroughly screening them using the California Mastitis Test (CMT) and milk somatic cell counts (SCC). This was followed by detailed milk composition analysis, differential leukocyte counts (DLC), and microbiological culture.ResultsThe differential gene expression of milk SCs through transcriptome profiling identified 83 and 76, up-regulated and 157 and 192 down-regulated genes in CM vs H and SCM vs H groups (log2 fold change ≥1 and ≤-1, p < 0.05) respectively. Pathway analysis revealed that upregulated genes were enriched in pathways such as phagosome activity, IL-17 signalling, Th1 and Th2 cell differentiation, while downregulated genes were linked to RIG-I-like receptor signalling, NK cell cytotoxicity, and Toll-like receptor signalling and Cytokine-cytokine receptor interactions. Notably, the study underscores the roles of chemokines CCL8, CCL2, and CXCL10 in immune cell recruitment during mastitis, where their downregulation suggests impaired mammary immune defense that governs Chemokine signalling pathways. Further, the comparative analysis with the previously available milk SCs proteome data identified the downregulation of chemokines signalling pathways during mastitis.DiscussionOverall, this research enhances our understanding of mastitis pathogenesis and emphasizes that these targeted chemokines may boost mammary resilience through immunomodulation, genetic selection and genome editing or by utilising adjuvants in vaccine development that restore chemokine signalling offers a potential strategy to improve mastitis resistance in dairy cattle.